Women’s Cinema in Contemporary Portugal. - Duarte, José (Imagofagia, 2021)
Sobre Mariana Liz e Hilary Owen. Women’s Cinema in Contemporary Portugal. New York: Bloomsbury, 2020, 272 pp. ISBN: 9781501349737.